A Multimodal Analysis on Rick Singer from Operation Varsity Blues: The College Admissions Scandal - Anastasya Chandraputri Sethio; Aylanda Hidayati Dwi Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
Multimodal communication employs multiple semiotic modes to convey meaning. Operation Varsity Blues: The College Admissions Scandal is a documentary about Rick Singer, an education entrepreneur who committed the bribes. This study analyzed his representation through the oral and visual modes and was aimed at showing how multimodality could help reveal particular character representations. This study applies multimodal theory (Kress & Leeuwen, 2006) and semiotic modes (Chia & Chan, 2017). The oral monologues and dialogues, and the visuals of people, objects, and places were scrutinized to observe how Rick Singer was depicted. As a result, he was seen being portrayed as a wealthy and successful entrepreneur with many high-ranking connections, who strategically manipulated his clients and his university partners in a clever scheming maneuver. The interplay of both the oral and visual modes has resulted in a relatively complete picture of the main actor of this documentary.